Academy of breastfeeding medicine founder's lecture 2011: inequalities and inequities in breastfeeding: an international perspective. - Cattaneo, Adriano (Breastfeed Med, 2012)
Breastfeeding is the biological norm for infant feeding but is also a social construct. As such, its rates and practices are determined by the same social determinants that shape health inequalities and inequities. In the past 30 years, several reports have drawn attention to the changing pattern of breastfeeding inequalities across countries and population groups. Breastfeeding rates tend to fall and rise following a similar pattern everywhere, although at different times and speed. The role of women within families and societies, the routines of maternity hospitals and other healthcare services, and the pressure exerted by the baby food industry are among the factors that influence the time and speed of changes in breastfeeding rates and practices across countries and population groups. Inequities (i.e., inequalities considered unfair and avoidable by reasonable action) can be redressed by interventions for the protection, promotion, and support of breastfeeding. Evidence-based and quality-implemented support and promotion activities, if applied without an equity lens, may increase inequities. Activities for the protection of breastfeeding (e.g., implementation and enforcement of the International Code of Marketing of Breastmilk Substitutes; legislations, regulations, and policies to remove obstacles and barriers to good-quality breastfeeding support and to protect women and mothers in the workforce; elimination of obstacles and barriers to breastfeeding anywhere, anyhow, and anytime mothers want) apply to all women and are less dependent on take up by the target population. If well designed and enforced, protective interventions contribute to reducing inequalities and inequities and to delivering promotion and support activities more effectively.
Keywords: Breast Feeding; Cross-Cultural Comparison; Female; Health Policy; Health Promotion; Healthcare Disparities; Humans; Infant Food; Infant, Newborn; Internationality; Maternal Health Services; Mothers; Pregnancy; Socioeconomic Factors